The circadian clock sets a spatial–temporal window for recent thymic emigrants. Issue 9 (15th September 2022) - Minaduola, Mili; Aili, Abudureyimujiang; Bao, Yuhui; Peng, Zhi; Ge, Qing; Jin, Rong
Abstract: The diurnal timing system regulates multiple functions of lymphocytes in peripheral lymphoid organs. Whether T‐cell development in the thymus and T‐cell egress from the thymus are affected by the circadian clock is not clear. Herein, we used flow cytometry to examine the cell number and percentage of total thymocytes and various thymocyte subsets from Zeitgeber time (ZT) 1 to ZT21. CD4 and CD8 single‐positive (SP) thymocytes, in particular, the mature CD4 SP4 thymocyte subset with emigration capability and P‐phycoerythrin + CD4 SP thymocytes in the perivascular space of the thymus, exhibited robust circadian oscillations. The diurnal expression of sphingosine‐1‐phosphate receptor‐1 (S1PR1) and CCR2 on SP thymocytes and the rhythmic sphingosine‐1‐phosphate (S1P) and CCL2 gradient formed between peripheral blood and thymus likely promoted SP thymocyte egress in a circadian pattern. Switching the daylight cycle disturbed the rhythm of S1PR1 and CCR2 expression and subsequent thymocyte output. We further demonstrated that the core clock molecule BMAL1 had rhythmic binding of the promoters of Klf2, S1pr1 and Sphk2 . Together, we elucidated the circadian dynamic characteristics of mature thymocyte egress, which coordinated with the diurnal changes in T‐cell homing to the lymph nodes. The core rhythmic molecule BMAL1 likely promoted thymocyte emigration through transcriptional regulation of emigration‐related molecules. Abstract : In this study, we found the egress of mature CD4 SP thymocytes had the circadian oscillation, which was associated with the diurnal changes of Foxo1, S1pr1, Sphk2 and Stat3 in a BMAL1‐dependent manner.